Pengaruh Product Information Quality dan Electronic Word-Of-Mouth (E-Wom) Terhadap Purchase Intention pada Platform Tiktok Shop di Indonesia dengan Customer Trust sebagai Mediasi - Mandala, Miko; Afifah, Nur; Giriati, Giriati; Purmono, Bintoro Bagus; Setiawan, Harry (Lembaga Publikasi Ilmiah Nusantara, 2025)
The rapid growth of e-commerce has made consumers increasingly dependent on digital information in making purchasing decisions. TikTok Shop, as a growing social commerce platform in Indonesia, presents an interactive video-based shopping experience that influences consumer behavior. This study examines the effect of Product Information Quality and Electronic Word-of-Mouth (e-WOM) on Purchase Intention in TikTok Shop, with Customer Trust as a mediating variable. Data were collected through an online questionnaire from 200 respondents selected by purposive sampling. The analysis was conducted using PLS-SEM with SmartPLS 4 software. The results showed that Product Information Quality and e-WOM had a positive and significant effect on Purchase Intention, both directly and through Customer Trust. Customer Trust acts as a mediator that strengthens the influence of product information and e-WOM on purchase intention. These results emphasize the importance of building consumer trust through credible information and positive reviews in TikTok Shop, as well as providing theoretical contributions to the social commerce literature and strategic references for digital entrepreneurs.